2010
DOI: 10.1111/j.1600-065x.2010.00912.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms that determine plasma cell lifespan and the duration of humoral immunity

Abstract: Humoral immunity following vaccination or infection is mainly derived from two types of cells: memory B cells and plasma cells. Memory B cells do not actively secrete antibody but instead maintain their immunoglobulin in the membrane-bound form that serves as the antigen-specific B-cell receptor. In contrast, plasma cells are terminally differentiated cells that no longer express surface-bound immunoglobulin but continuously secrete antibody without requiring further antigenic stimulation. Pre-existing serum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
260
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(277 citation statements)
references
References 96 publications
12
260
3
2
Order By: Relevance
“…Although persistence of vaccine-elicited antibody responses has been known for many years (discussed in refs. 55,56), it was investigated, to our knowledge, for the first time using modern immunological methods in two studies of immunity to vaccinia (57,58), where antibody responses were found to persist for decades after immunization. This observation was confirmed and extended in a comprehensive analysis of antibody persistence to common vaccines and infections (55).…”
Section: Strategies To Elicit Continuous Protection Against Hiv By Vamentioning
confidence: 99%
See 2 more Smart Citations
“…Although persistence of vaccine-elicited antibody responses has been known for many years (discussed in refs. 55,56), it was investigated, to our knowledge, for the first time using modern immunological methods in two studies of immunity to vaccinia (57,58), where antibody responses were found to persist for decades after immunization. This observation was confirmed and extended in a comprehensive analysis of antibody persistence to common vaccines and infections (55).…”
Section: Strategies To Elicit Continuous Protection Against Hiv By Vamentioning
confidence: 99%
“…1 (adapted from figure 3 in ref. 56). Three distinct zones of plasma antibody concentration are apparent after vaccination.…”
Section: Strategies To Elicit Continuous Protection Against Hiv By Vamentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo exposure to cognate antigens (in the form of reinfection or booster vaccination) results in the activation of memory B cells and their subsequent proliferation and differentiation into antibody-secreting daughter cells. 21,22 To assess whether the impaired B-cell proliferation could affect the capacity of memory B cells to differentiate into ASCs, we measured the in vitro differentiation of total PBMCs after stimulation with PWM and CpG alone or in combination (Fig 4, A).…”
Section: Impaired Proliferation Is Associated With Lower Frequencies mentioning
confidence: 99%
“…This theory suggests that PC life span is dependent on the strength of combined B cell signals experienced by the cell during the encounter with antigen. 46 Mechanisms of long-term maintenance of B MEM are also still unclear but most likely rely on antigen-independent processes. 47 While some studies have demonstrated a relationship between B MEM and antibody concentration at various intervals after immunization this has not been consistent for all antigens or between studies.…”
Section: Correlation Of B Cell Responses To Antibody Concentrationsmentioning
confidence: 99%